ISLAMIC CHARACTERS EDUCATION CONSTRUCT OF YOUNG GENERATION BASED ON LOCAL CULTURAL VALUES OF LAMPUNG INDIGENOUS PEOPLES - Syaripudin Basyar; Zulhannan Zulhannan; Ahmad Muzakki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2020)
This paper describes the construct of Islamic character education based on the local culture of the indigenous Lampung people. Four constructs of character education are presented in the Piil Pesenggiri, namely Nemui Nyimah which contains the character of a sense of acceptance, including; hospitality, hospitality, generosity, courtesy, mutual respect, respect, love for friendship, submission and submission to the Creator of the Universe and His creations. Nengah Nyappur contains adaptive character values ​​in interacting, including; willingness to open up, have a high tolerance, like to deliberate, have an attitude and sociable behavior, easy to get along with, familiar or friendly, and a sense of family. Sakai Sambaiyan contains high solidarity character values, including; mutual assistance, please help, work together, give each other something that is needed by the other party. Juluk Adok contains the spirit of achievement character values, including; persistent and hard working, likes to participate, has an honorary degree. In the context of education, Piil Pesenggiri becomes an inseparable part of the realization of the nation's character education. Piil Pesenggiri becomes a principle of self-esteem which is the culmination and reflection of the accumulation of noble and noble forms of activity amid society. In the context of geneology education in the character of Lampung indigenous people, Piil Pesenggiri can be a measure or dignity for someone amid their life activities. Substantially, Piil Pesenggiri in the context of character education becomes the